INDICATIONS OF PRIMARY CAESAREAN SECTIONS AMONG IRAQI WOMEN IN KARBALA CITY DURING 2018 - MOHAMMAD, EMAN MAHDI; AL-GHABBAN, SAAD IBRAHIM; AL-ALAK, MOUSA MOHSIN (International Journal of Current Pharmaceutical Research, 2019)
Objective: To study the different indications of primary caesarean sections for women attending Karbala Maternity Teaching Hospital and Al-kafeel Super Specialty hospital. Methods: This was cross-sectional study, the sample was 330 women. Over the period from 1st January 2018 to [30]th June 2018. Questionnaire was filled by direct interviews. A pilot study was done; the subjects of the pilot including 20 women with previous PCS, and some modifications were occurred done accordingly. The sample of study was convenient sample including all women for whom PCS was done in the first time, it was 330 women. Then data was entered and analyzed by SPSS program version 22. Results: The commonest age group in this study was (25-29) year, which represent 32.1%. Majority of the study sample (49.7%) were primigravida. The percentage of indications of Caesarean section include fetal distress 22.1%, prolonged labor18.5%, malpresentation 17.3% and amniotic fluid leakage 16.4%. Emergency CS had 43.6%, and maternal request had 21.5%. Conclusion: Largest number of participant were primigravidarum which read big and serious problem for women life in future. Most women had taken regular antenatal care. Fetal distress and prolonged labor were the most common indications for caesarean section. Fetal outcome was good that reflect good antenatal care and perinatal care.